Manufacturing processes and systems selected, peer reviewed papers from the 2010 International Conference on Advances in Materials and Manufacturing Processes (ICAMMP 2010), 6-8 November, 2010, Shenzhen, China - Liu, Xianghua; Jiang, Zhengyi; Han, Jingtao (Trans Tech Publications, 2010)
"This book aims to collect the latest advancement and applications of computer numerical control systems, operations planning, geometric dimensioning and tolerancing, quality systems, basic machine tool elements, process automation, operator-machine systems, cost estimating, metrology and testing, etc."--Pref.
Keywords: Manufacturing processes -- Congresses.; elektronické knihy; electronic books